Examining the Correlation between School Support and Teachers’ Implementation of Inclusive Education - Talipan, Elvin A.; Tenerife, Janine Joy L.; Sitoy, Regina E.; Capuno, Reylan G.; Taghoy, Julius; Espina, Raymond C.; Mamites, Irene O. (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study investigated the relationship between teachers perceived school support and their implementation of inclusive education at Alaska Night High School during the 2025–2026 school year, serving as the basis for a proposed Action Plan. The demographic characteristics of the respondents—including age, gender, educational attainment, length of service, and teaching position—were collected to provide context for interpreting the findings. Data were gathered using a structured survey that assessed teachers’ perceptions of school support and the extent to which inclusive education practices were applied in classrooms. Descriptive statistics, such as frequency counts, percentages, and weighted means, were used to analyze levels of support and implementation, while Pearson’s correlation coefficient was employed to determine the significance of the relationship between the two variables. Findings revealed that the teaching workforce was predominantly female and young, with most teachers holding a bachelor’s degree and occupying lower to mid-level positions. Teachers reported strong school support, particularly in areas such as access to training programs, collaboration with SPED specialists, and administrative encouragement for inclusive practices. The extent of implementation of inclusive education was high, with teachers regularly modifying instruction, differentiating lessons, involving parents, adapting classroom setups, and providing individualized support. Correlation analysis indicated a strong positive and statistically significant relationship between perceived school support and inclusive education implementation, The study concluded that school support plays a crucial role in enhancing teachers’ inclusive practices. It is recommended that Alaska Night High School develop and implement an Action Plan to further strengthen school support, ensuring the sustained and effective application of inclusive education strategies.